2010
DOI: 10.1167/10.6.8
|View full text |Cite
|
Sign up to set email alerts
|

High-capacity, transient retention of direction-of-motion information for multiple moving objects

Abstract: The multiple-object tracking paradigm (MOT) has been used extensively for studying dynamic visual attention, but the basic mechanisms which subserve this capability are as yet unknown. Among the unresolved issues surrounding MOT are the relative importance of motion (as opposed to positional) information and the role of various memory mechanisms. We sought to quantify the capacity and dynamics for retention of direction-of-motion information when viewing a multiple-object motion stimulus similar to those used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…Specifically, making conservative predictions is consistent with work demonstrating that observers are sensitive to and can report object bearing accurately, on average, but with a great deal of noise in many situations (Horowitz & Cohen 2010;Shooner et al, 2010;St. Clair et al, 2010).…”
Section: Do Human Observers Extrapolate In Mot?supporting
confidence: 79%
See 1 more Smart Citation
“…Specifically, making conservative predictions is consistent with work demonstrating that observers are sensitive to and can report object bearing accurately, on average, but with a great deal of noise in many situations (Horowitz & Cohen 2010;Shooner et al, 2010;St. Clair et al, 2010).…”
Section: Do Human Observers Extrapolate In Mot?supporting
confidence: 79%
“…In particular, several studies have shown that human observers possess the raw materials necessary for extrapolation. They can report (albeit with noise) the direction of a target's motion in an MOT trial (Horowitz & Cohen, 2010;Iordanescu, Graboweky, & Suzuki, 2009;Shooner, Tripathy, Bedell, &Ögmen, 2010). One study even demonstrated that a moving pattern within an object can impair tracking if it moves against the object's trajectory, suggesting an automatic encoding of bearing (St. Clair, Huff, & Seiffert, 2010) and a cost caused by signals that make this encoding difficult.…”
Section: Do Observers Extrapolate When Doing Mot?mentioning
confidence: 99%
“…Greater allocation of the attentional enhancement resource to a target might result in greater precision of target localization (Alvarez & Franconeri, 2007) and greater precision of motion direction representation, which would facilitate tracking the target. Both precision of target localization (Howard & Holcombe, 2008) and motion direction representation Shooner, Tripathy, Bedell, & Öğmen, 2010) in MOT have been found to decrease with increased number of targets, and precision of target localization has been found to decrease with increased speed (Howard, Masom, & Holcombe, 2011). These findings suggest that the precision of these representations is dependent on a limited resource.…”
Section: Discussionmentioning
confidence: 80%
“…Tracking tasks that involve the detection of deviations of motion trajectories depend on sensory memory of the motion trajectory, as they require the comparison of a current motion direction to the just-observed motion direction (Narasimhan, Tripathy, & Barrett, 2009). Possibly, such memory traces also play a role during classic MOT tasks (Shooner, Tripathy, Bedell, & Ogmen, 2010). Prominent age-related declines, starting at age 30, have been observed in the ability to detect deviations of linear motion trajectories in the absence of distractor objects (Kennedy, Tripathy, & Barrett, 2009).…”
Section: Discussionmentioning
confidence: 99%